Detection of human parvovirus B19 in children with acute hepatitis - Aydin, M; Bulut, Y; Poyrazoglu, G; Turgut, M; Seyrek, A (Maney Publishing, 2006)
Parvovirus is a rare cause of acute hepatitis. Two children with non A-E acute hepatitis in whom human parvovirus B19 was detected by PCR are reported.
Keywords: Fulminant-Hepatitis; Infection